2000
DOI: 10.4049/jimmunol.165.11.6170
|View full text |Cite
|
Sign up to set email alerts
|

The TNF Receptor Family Member CD30 Is Not Essential for Negative Selection

Abstract: CD30 is a member of the TNF receptor superfamily that has been implicated in negative selection and some forms of peripheral tolerance. A previous study of CD30−/− mice in a class I-restricted H-Y TCR-transgenic mouse model showed that CD30 is essential for removal of autoreactive thymocytes. During the course of the studies of CD30 in the class II-restricted TCR-transgenic mice, we found that the absence of CD30 has no effect on negative selection. Surprisingly, we also found that the CD30 mutation does not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…CD30, another TNF receptor superfamily member originally suggested to be involved in negative selection [48] was later shown not to be involved in this process [49].…”
Section: Apoptosis In the Immune System Central Tolerance -Education mentioning
confidence: 99%
“…CD30, another TNF receptor superfamily member originally suggested to be involved in negative selection [48] was later shown not to be involved in this process [49].…”
Section: Apoptosis In the Immune System Central Tolerance -Education mentioning
confidence: 99%
“…CD30-deficient mice have been reported to have a defect in negative selection (10), and overexpression of CD30 on T cells results in augmented thymocyte depletion upon treatment with superantigen or antigenic peptide (11). However, a more recent study failed to confirm decreased negative selection in independently generated CD30-deficient mice (12), suggesting an alternative, as yet unidentified, role for CD30 in vivo.…”
mentioning
confidence: 99%
“…Experiments using CD30-deficient mice have indicated that this molecule is involved in the deletion of autoreactive thymocytes (22,23), whereas a recent report denied this function (24). TNFR family members can transduce signals when surface molecules are appropriately cross-linked.…”
mentioning
confidence: 99%